Fluorescent Labeling of Calmodulin with Bifunctional Rhodamine - Beausang, John F. (2012)
Polarized total internal reflection fluorescence microscopy (polTIRFM) can be used to detect the spatial orientation and rotational dynamics of single molecules. polTIRFM determines the threed-imensional angular orientation and the extent of wobble of a fluorescent probe bound to the macromolecule of interest. This protocol describes how to label chicken calmodulin (CaM) with bifunctional rhodamine (BR) at two engineered cysteine (Cys) residues (P66C and A73C) so that it cross-links the two Cys sites. The resulting BR-CaM protein is then purified by high-performance liquid chromatography (HPLC) and concentrated by filter centrifugation. To confirm that the two Cys residues in the labeled CaM are actually cross-linked by BR, a sample of purified BR-CaM is digested by an endoproteinase and analyzed by mass spectrometry. The BR-CaM can then be used to label myosin V, which can in turn be used in a polTIRFM processive motility assay.